2021
DOI: 10.1007/s00216-021-03699-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic network-based identification of plasma markers for non-small cell lung cancer

Abstract: Metabolic markers, offering sensitive information on biological dysfunction, play important roles in diagnosing and treating cancers. However, the discovery of effective markers is limited by the lack of well-established metabolite selection approaches. Here, we propose a network-based strategy to uncover the metabolic markers with potential clinical availability for non-small cell lung cancer (NSCLC). First, an integrated mass spectrometry-based untargeted metabolomics was used to profile the plasma samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Similarly, ACSL5 has potential prognostic value in a variety of tumors. For instance, sporadic colorectal adenocarcinoma may have an independent prognostic marker for early recurrence called ACSL5 [17]. Patients with both ER-positive and ER-negative breast cancer may have a better prognosis if ACSL5 is highly expressed [18].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ACSL5 has potential prognostic value in a variety of tumors. For instance, sporadic colorectal adenocarcinoma may have an independent prognostic marker for early recurrence called ACSL5 [17]. Patients with both ER-positive and ER-negative breast cancer may have a better prognosis if ACSL5 is highly expressed [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ACOT 7, ACOT 2 has also been implicated in NSCLC, and Guo et al. ( 35 ) demonstrated based on the human metabolic network that ACOT 2 can participate as a potential molecular target of NSCLC in the metabolic pathways of aromatic amino acids and long-chain fatty acids.…”
Section: Progress Of Acots In Cancermentioning
confidence: 99%
“…In another study, by combining differential metabolites obtained by MS with a metabolic network based on Kyoto Encyclopedia of Genes and Genomes database, Guo et al. constructed a metabolite panel (including pyruvate) specifically for non-small cell lung cancer (NSCLC) with a diagnostic accuracy of almost 98% ( 19 ). Subsequently, by applying the NMR technique, Ye et al.…”
Section: Metabolomic Biomarkers For Cancer Screening and Diagnosismentioning
confidence: 99%
“…Abnormalities in tryptophan metabolism in tumor cells have been extensively studied and metabolites involved in tryptophan catabolism, such as kynurenine, have emerged as targets for anti-tumor therapy ( 102 ). Alterations in tryptophan levels in the biological fluids of lung cancer patients have been observed in three studies, two of which found that patients with NSCLC had elevated blood tryptophan levels compared to healthy controls ( 19 , 43 ). In contrast, a study based on sputum metabolomics observed the opposite trend in patients with lung cancer ( 46 ), and the difference in the distribution of tryptophan in blood and sputum may be the result of increased tryptophan consumption by tumor cells.…”
Section: Metabolomic Biomarkers For Cancer Screening and Diagnosismentioning
confidence: 99%